Intraductal xenografts show lobular carcinoma cells rely on their own extracellular matrix and LOXL1. Issue 3 (22nd February 2021) - Sflomos, George; Battista, Laura; Aouad, Patrick; De Martino, Fabio; Scabia, Valentina; Stravodimou, Athina; Ayyanan, Ayyakkannu; Ifticene‐Treboux, Assia; ,; Bucher, Philipp; Fiche, Maryse; Ambrosini, Giovanna; et al.
Abstract: Invasive lobular carcinoma (ILC) is the most frequent special histological subtype of breast cancer, typically characterized by loss of E‐cadherin. It has clinical features distinct from other estrogen receptor‐positive (ER + ) breast cancers but the molecular mechanisms underlying its characteristic biology are poorly understood because we lack experimental models to study them. Here, we recapitulate the human disease, including its metastatic pattern, by grafting ILC‐derived breast cancer cell lines, SUM‐44 PE and MDA‐MB‐134‐VI cells, into the mouse milk ducts. Using patient‐derived intraductal xenografts from lobular and non‐lobular ER + HER2 − tumors to compare global gene expression, we identify extracellular matrix modulation as a lobular carcinoma cell‐intrinsic trait. Analysis of TCGA patient datasets shows matrisome signature is enriched in lobular carcinomas with overexpression of elastin, collagens, and the collagen modifying enzyme LOXL1 . Treatment with the pan LOX inhibitor BAPN and silencing of LOXL1 expression decrease tumor growth, invasion, and metastasis by disrupting ECM structure resulting in decreased ER signaling. We conclude that LOXL1 inhibition is a promising therapeutic strategy for ILC. Synopsis: Intraductal xenografts of invasive lobular carcinoma (ILC) cells faithfully model this breast cancer subtype, and reveal tumor cell intrinsic ECM remodeling as a critical feature of disease progression that can be exploited therapeutically by targeting LOXL1. In vivo ILC models from MDA‐MB134 and SUM44 cell lines are developed and characterized. Additional ILC PDX models are established through the intraductal xenografting approach. Global gene expression profiling reveals ECM remodeling as a key tumor cell intrinsic ILC feature. ILC patient tumors show enhanced ECM production and LOXL1 expression. Inhibition of LOXL1 slows tumor progression in preclinical ILC models. Abstract : Intraductal xenografts of invasive lobular carcinoma (ILC) cells faithfully model this breast cancer subtype, and reveal tumor cell intrinsic ECM remodeling as a critical feature of disease progression that can be exploited therapeutically by targeting LOXL1.